The prevalence of Listeria monocytogenes in meat products in Brazil: A systematic literature review and meta-analysis. (July 2022) - Cavalcanti, Aline Antas Cordeiro; Limeira, Clécio Henrique; Siqueira, Iara Nunes de; Lima, Aldenir Cavalcanti de; Medeiros, Filipe Jordão Pereira de; Souza, Joyce Galvão de; Medeiros, Nara Geanne de Araújo; Oliveira Filho, Abrahão Alves de; Melo, Marcia Almeida de
Abstract: Listeria monocytogenes, a foodborne pathogen that causes human listeriosis, is commonly found in meat products. This study aimed to estimate the prevalence of L. monocytogenes in a variety of Brazilian meat products, using a meta-analysis of data from the literature. A total of 29 publications from five databases, published between January 1, 2009, and December 31, 2019, were included in the study. Estimated by the random-effects model, the combined prevalence of L. monocytogenes was 13%, ranging from 0 to 59%. The combined prevalence of L. monocytogenes was 14% and 11% for raw meat and ready-to-eat (RTE) meat, respectively. The prevalence of L. monocytogenes was higher in the swine species' meat products and the Southeast region of Brazil. Regarding the type of establishment, it was the retail market that presented the highest combined prevalence rate (19%). The most prevalent serotypes of L. monocytogenes were 4b, 1/2a, 1/2b, and 1/2c. The knowledge of differences in the prevalence levels of L. monocytogenes in different meat products can guide in its efficient control by the competent authorities and by industry. Highlights: The combined prevalence of L. monocytogenes in Brazil's meat products was 13%. The prevalence of L. monocytogenes in raw meat was higher than ready-to-eat meat. The highest prevalence of L. monocytogenes was in pork meat products. Retail meat products showed higher prevalence than the industry. Southeast region of Brazil showed higher L. monocytogenes prevalence.